Relationship between Respondent Characteristics and Noise Intensity with Increased Blood Pressure in Production Unit Workers of PT Japfa Comfeed Indonesia, Tbk. Plant Margomulyo - Sofia, Sofia; Dwiyanti, Endang; Oksigendaru Dicha, Nisrina; Thrisiawan Pradhana, Andrea (Jurnal Ilmiah Kesehatan, 2024)
The most common physical risk at work is noise, which may cause several health issues. These include diseases of the auditory system and non-auditory impacts including poor communication, tension, anxiety, high blood pressure, and decreased productivity. At the production unit of PT Japfa Comfeed Indonesia, Tbk. Plant Margomulyo, this research aimed to examine the association between respondent characteristics and noise intensity in the workplace and changes in workers' blood pressure before and after work. 51 respondents participated in the cross-sectional study using an analytical and observational methodology. The results showed that elevated blood pressure was significantly correlated with age (p = 0.000), duration of service (p = 0.007), usage of personal protective equipment (PPE) (p = 0.011), and noise intensity (p = 0.000). Nonetheless, no statistically significant correlation was seen between elevated blood pressure and dietary state (p = 0.467), smoking behaviors (p = 0.763), or history of hypertension (p = 0.170). These findings suggest that while lifestyle factors like smoking and nutritional status have less impact in this context, occupational factors— particularly noise exposure—as well as certain personal characteristics like age and length of service are linked to elevated blood pressure in workers.